Metformin use is associated with low risk of case fatality and disability rates in first-ever stroke patients with type 2 diabetes - Wen-Jun Tu; Zheng Liu; Bao-Hua Chao; Feng Yan; Lin Ma; Lei Cao; Xun-Ming Ji; Long-De Wang (SAGE Publishing, 2022)
Background: To assess the effectiveness of metformin treatment on long-term outcomes in first-ever stroke patients with type 2 diabetes mellitus (T2DM) in China. Methods: From August to September 2019, all patients with first-ever stroke and T2DM from 232 hospitals in China Mainland were included. The enrolled patients were divided into two groups: the metformin treatment (MT) and the no-metformin treatment (No-MT) groups. All discharged patients would receive a telephone follow-up at 12-month after admission. Results: In total, 7587 first-ever stroke patients with T2DM [age: median (IQR) = 66 (57-73) years; 57.35% male] were recruited. Out of those 7587 included patients, 3593 (47.36%) received MT. The in-hospital case fatality rate was lower in the MT group than the No-MT group [MT group versus No-MT group: 1.09% versus 2.30%; absolute difference = −1.75% (95% CI = −2.15 to −1.17%); OR = 0.63 (95% CI = 0.47 to 0.84)]. The 12-month case fatality rate was lower in the MT group than the No-MT group [4.72% versus 8.05%; absolute difference = −4.05% (95% CI = −5.58 to −2.41); OR = 0.69 (95% CI = 0.50 to 0.88)]. The 12-month disability rate was also lower in the MT group than the No-MT group [14.74% versus 19.41%; absolute difference = −5.70% (95% CI = −7.25 to −3.22); OR = 0.83 (95% CI = 0.70 to 0.95)]. Furthermore, the recurrence rate did not differ significantly between the MT and No-MT groups ( p  = 0.29). Conclusion: The study reveals that metformin use in stroke patients with T2DM results in a less severe stroke and lower fatality and disability rates.